ANALISIS KERUSAKAN ERETAN MEJA PADA MESIN SEKRAP TIPE KLOOP MODEL 525 - Iqbal Khumaidillah; Jatira; Choirul Anwar (Sekolah Tinggi Teknologi Wastukancana, 2023)
The development of science and technology has an important role in the success of development in the industrial sector. In the industrial world, machining processes are very important. A scrap machine is a machine tool that is used to change the surface of a workpiece into a flat surface with levels, corners and grooves.This research aims to find out the causes of damage to the automatic movement of the table, to determine the strength of the material using impact testing and calculating torsional moments, and to be able to repair damage using the welding method using brass. Damage that occurs to the automatic movement of the table is caused by the final limit of the moving table being exceeded. On a sledding table there is no final limit for the moving table, when the final limit for the moving table occurs, the automatic moving machine continues to work and exceeds the material strength limit of 14,133 joules and 1422 N.m, causing the nut to be damaged. Repairing the sliding table nut is done by welding. This welding is carried out using brass, brass is used because it has high wear resistance. Keywords: Scrap Machine, torsional moment, impact test, cause of damage.